Pregnancy in Overt and Subclinical Hypothyroidism and its Feto-Maternal Outcome - Akhter, Syeda Nazia; Tarannum, Rebeka; Kabir, Mohammed Shafiqul (Medicine Today, 2014)
This prospective study was done to find out the maternal and fetal complications of pregnancy in patients with subclinical and overt (TSH level higher than subclinical hypothyroidism) hypothyroidism. Chronic hypertension, anemia with GDM, GDM with preeclampsia and thalassemia with GDM were observed only in patients with overt hypothyroidism. PPH, fetal distress, abortion and IUD were significantly higher (p<0.05) in patients with overt hypothyroidism. Fetal distress was found to be more in patients with overt than subclinical hypothyroidism. This study included 50 admitted patients who were pregnant. Among which, 29 were diagnosed as cases of subclinical hypothyroidism and 21 as that of overt hypothyroidism. Duration of marriage was almost identical between two groups. Multipara was predominant in both groups, however abortions were significantly higher (p<0.05) in overt hypothyroidism. Duration between first conception and marriage was somewhat longer (3-5 years) in patients with overt hypothyroidism than that ( 2 years) in patients with subclinical hypothyroidism. The commonest problem in both groups was anemia. 17.2% of patients with subclinical hypothyroidism were anemic whereas 42.9% patients with overt hypothyroidism suffered anemia. Preeclampsia (23.8%) and diabetes mellitus (38.1%) were also predominant in patients with overt hypothyroidism than in patients with subclinical hypothyroidism (Preeclampsia-3.4% and DM-10.3%). Low Birth Weight (LBW) babies were also common in patients with overt hypothyroidism (80%) than in patients with subclinical hypothyroidism (27.6%). 62.1% of babies from mothers having subclinical hypothyroidism had APGAR score of 7 whereas 73.3% of babies from mothers having overt hypothyroidism had APGAR score of 6 in the first minute. None of the babies were hypothyroid as tested from cord blood. Majority of patients underwent C-section in both groups. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17924 Medicine Today 2013 Vol.25(2): 69-71